The Visual dictionary of plants. - Dorling Kindersley Publishing, Inc. (New York : Dorling Kindersley, 1992)
Text and labeled illustrations depict a variety of plants and their parts, including woody, flowering, desert, and tropical plants.
Includes index.
Keywords: Plants -- Terminology -- Juvenile literature; Plants -- Pictorial works -- Juvenile literature; Picture dictionaries, English -- Juvenile literature; Plants